Peran Kemampuan Berpikir Kritis terhadap Partisipasi dan Hasil Belajar Matematika Siswa Sekolah Dasar: Analisis Mediasi dan Moderasi - Nurlaili; Mohammad Archi Maulyda; Nurkhaerat Alimuddin (Mataram University, 2026)
Mathematics learning in elementary school requires not only active participation but also higher-order thinking skills to achieve meaningful learning outcomes. Critical thinking skills are considered essential in helping students analyze problems and construct logical solutions. This study aimed to analyze the role of critical thinking skills on students’ participation and mathematics learning outcomes through mediation and moderation analysis. The study employed a quantitative explanatory design involving 141 students from grades IV, V, and VI at SDN 27 Cakranegara. Data were collected using questionnaires, tests, and documentation techniques. The data were analyzed using direct effect, indirect effect, moderation, and ANCOVA analyses. The direct effect analysis showed that participation did not significantly affect mathematics learning outcomes (0.051 > 0.05), indicating that participation alone was insufficient to improve students’ achievement. In contrast, critical thinking skills had a positive and significant effect on mathematics learning outcomes (0.002 < 0.05), showing that students with higher critical thinking abilities achieved better learning outcomes. The mediation analysis revealed that critical thinking skills significantly mediated the relationship between participation and mathematics learning outcomes (0.02 < 0.05). However, the moderation analysis indicated that critical thinking skills did not significantly moderate the relationship between participation and learning outcomes (0.696 > 0.05).